Implied volatility forecasting in the options market: a survey - Mohamad, Azhar (Penerbit UTM Press, 2016)
Implied volatility is regarded as one of the most important variables for determining profitability in options trading. Implied volatility gives indication about the future volatility of the underlying asset and can be used to predict the degree to which the asset price might swing and thus whether the options could become profitable before expiration. Volatility forecasting can be grouped into two main categories namely option-implied volatility and historical time-series models. There is an academic debate as to which of the two methods has stronger predictive power. In this paper, we provide a review of options-implied volatility forecasting studies. This survey of the literature suggests there is no consensus to indicate that the implied volatility has stronger predictive power than historical time series in forecasting realized volatility.